Biochar and rice straw have different effects on soil productivity, greenhouse gas emission and carbon sequestration in Northeast Thailand paddy soil - Thammasom, Nipa; Vityakon, Patma; Lawongsa, Phrueksa; Saenjan, Patcharee (Agriculture and Natural Resources, 2016)
This study aimed to clarify the effects of biochar (BC made from Eucalyptus camaldulensis Dehnh.), and rice (Orysa sativa L.) straw (RS) amendments on the soil productivity, carbon sequestration (Cseq) and the possibility for mitigating greenhouse gas (GHG) emissions. A field trial was conducted with 10 treatments: the control, chemical fertilizer (CF) and BC or RS each at four rates of L (6.25 t/ha), ML (12.50 t/ha), MH (18.75 t/ha) and H (25.00 t/ha) using a randomized complete block design with four replicates. The results showed that BC and RS not only increased the soil quality but also increased the rice yield (RY). During the growing season, BC and RS applications did not differ in the total CO2 emission. However, the total CH4 emission and total global warming potential significantly decreased in the BC application and significantly increased in the RS application, relative to the control. Soil Cseq increased under the BC application by 1.87-13.37 t C/ha, while the RS application reduced Cseq by 0.92-2.56 t C/ha. The high amount of recalcitrant C molecules in BC probably explained the decreases in the GHG-C loss and increases in Cseq. In contrast, RS had high amounts of labile components that enhanced the GHG-C emission and reduced Cseq. Finally, the GHG intensity of rice production was reduced for both BC and RS meaning that these two amendments can be considered as good options for the mitigation of climate change.